# 5.5 - 5.5: The Substitution Rule (Dated: September 25,...

This preview shows pages 1–2. Sign up to view the full content.

5.5: The Substitution Rule (Dated: September 25, 2011) Theorem 1 (The Substitution Rule for Indeﬁnite Integrals) If u = g ( x ) is a differentiable function whose range is an interval I and f is continuous on I, then Z f ( g ( x )) g 0 ( x ) dx = Z f ( u ) du . Proof. Let F be an antiderivative of f ; that is, F 0 = f . Since ( F g ) 0 ( x ) = F 0 ( g ( x )) g 0 ( x ) by the chain rule, it follows from FTC that Z f ( g ( x )) g 0 ( x ) dx = Z F 0 ( g ( x )) g 0 ( x ) dx = Z ( F g ) 0 ( x ) dx = F ( g ( x )) + C = F ( u ) + C = Z F 0 ( u ) du = Z f ( u ) du . Example 1 (Selected exercises from exercises 5.5.7-5.5.46) Evaluate the indeﬁnite integrals. 8*: R x 2 ( x 3 + 5) 9 dx 11: R ( x + 1) p 2 x + x 2 dx Hint: u = 2 x + x 2 12*: R x ( x 2 + 1) 2 dx Hint: u = x 2 + 1 13*: R dx 5 - 3 x dx Hint: u = 5 - 3 x 18: R sec2 θ tan2 θ d θ Hint: u = 2 θ 19*: R (ln x ) 2 x dx Hint: u = ln x 21*: R cos p t p t dt Hint: u = p t 23*: R cos θ sin 6 θ d θ Hint: u = sin θ 25: R e x p 1 + e x dx Hint: u = 1 + e

This preview has intentionally blurred sections. Sign up to view the full version.

View Full Document
This is the end of the preview. Sign up to access the rest of the document.

## This note was uploaded on 11/11/2011 for the course MATH 152.01 taught by Professor Geline during the Fall '09 term at Ohio State.

### Page1 / 2

5.5 - 5.5: The Substitution Rule (Dated: September 25,...

This preview shows document pages 1 - 2. Sign up to view the full document.

View Full Document
Ask a homework question - tutors are online